Cloud-Enabled Administrative Systems and Operational Agility: An Empirical Analysis of Task Management and Data Accessibility Among Office Professionals - Dr. Bernard Olu Okoro; Dr. Chinwe Chioma Ebenezer-Nwokeji (International Journal of Multidisciplinary Research and Studies, 2026)
Cloud-enabled administrative systems are increasingly transforming administrative operations within financial institutions by enhancing task coordination, data accessibility, and operational flexibility. This study examined the influence of cloud-enabled administrative systems on operational agility among office professionals in selected commercial banks in Imo State, Nigeria. A descriptive survey design was employed, with data collected from 112 office professionals across major commercial banks using structured questionnaires. Descriptive statistics and regression analysis were applied to analyze relationships among cloud-enabled systems, task management efficiency, data accessibility, and operational agility. Results revealed high adoption of cloud-based administrative tools and significant positive relationships between cloud-enabled systems and task management efficiency (r = 0.689, p < 0.05) as well as data accessibility (r = 0.752, p < 0.05). Regression analysis further demonstrated that cloud-enabled administrative systems significantly predict operational agility (β = 0.781, p < 0.05), explaining 58.4% of its variance. These findings confirm that digital administrative infrastructure enhances workflow coordination, information accessibility, and organizational responsiveness. The study contributes to digital transformation literature by providing empirical evidence of micro-level administrative benefits of cloud technologies in the banking sector. Practical implications suggest that financial institutions should prioritize digital infrastructure investments and capacity-building initiatives to optimize administrative performance and operational adaptability. DOI:-10.5281/zenodo.19081099